Evaluation of Clinical Use and Cost-Effectiveness of a Flexible Cystoscope System with a Disposable Sheath: A Randomized Clinical Trial. Issue 4 (July 2019) - Zambon, Joao P.; Watkins, Thomas P.; Hemal, Ashok; Evans, Robert J.; Gutierrez-Aceves, Jorge; Mirzazadeh, Majid; Terlecki, Ryan P.; Deveshwar, Shaun P.; Hemal, Kshipra; Badlani, Gopal H.
Abstract: Introduction: Flexible cystoscopy is routinely performed as an outpatient procedure. The use of disposable sheaths can increase cystoscope life span and reduce staff costs. The primary end point of this study was to evaluate procedure related discomfort and pain, physician maneuverability, residual bioburden and reprocessing time. The secondary end point was to analyze the cost-effectiveness of a flexible cystoscope with a disposable sheath compared to a standard flexible cystoscope. Methods: This randomized clinical trial was performed with women older than 18 years, with intact cognition and 7 days antibiotic-free who were referred to outpatient clinic for cystoscopy. Patients underwent cystoscopy with a standard flexible cystoscope or flexible cystoscope with disposable sheath. Urinalysis and culture were performed before and 14 days after cystoscopy. Patients filled out a pain/discomfort visual analog scale. Physicians filled out a 5-point Likert scale for the elements of ease of insertion, manipulation, optical quality and overall use. Reprocessing time and costs were compared between both cystoscopes. Results: A total of 60 patients were included in the study, comprised of 30 who underwent standard flexible cystoscopy and 30 who underwent flexible cystoscopy with a protective sheath. Patient discomfort/pain was equivalent in both groups. The Likert scores were similar except for ease of insertion, which was higher with protective sheaths (p <0.02). Protective sheaths were associated with lower reprocessing time and costs (p <0.001). Conclusions: The use of protective sheaths effectively reduced procedure and staff related costs without causing any additional patient discomfort or pain. The learning curve of the sheathed scope may explain the difference reported by physicians regarding the ease of insertion.